A dictionary of statistical terms - Kendall, Maurice G.; Buckland, William R.; International Statistical Institute (Edinburgh : Published for the International Statistical Institute by Oliver and Boyd, 1971)
The dictionary is invaluable in looking up unexplained statistical terms that one may across in reading. This present edition takes account of literature in both book and journal form up to the end of 1968.
ne 09/09/2021
Ref.
Keywords: Statistics